1982
DOI: 10.1002/jcp.1041100207
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate concentration and transport in Ehrlich ascites tumor cells: Effect of sodium

Abstract: The effects of extracellular Pi and Na+ on cellular Pi concentration and transport were studied. Steady-state Pi exchange flux was measured by 32P uptake in the presence and absence of Na+. Model experiments were also conducted to assess the possibility that hydrolysis of organic phosphate esters contributes to the chemically measured intracellular Pi concentration of Ehrlich ascites tumor cells. The results of these experiments indicate that hydrolysis of labile organic phosphate esters does not contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Most of the intracellular radioactivity in the cultured cells was associated with purine nucleoside triphosphates and very little with monophosphates (Table 4). This relative independence of purine phosphoribosylation in the cultured cells on extracellular phosphate may be related to inherently higher intracellular levels of phosphate (5-15 mM; Bowen and Levinson, 1982;McIvor et al, 1985) and consequently of P-Rib-PP in these cells than found in erythrocytes as well as a tighter regulation of the intracellular phosphate concentration. For example, incubation of Novikoff cells in phosphate-free medium for several hours at 37°C has little effect on the intracellular phosphate concentration (McIvor et al, 1985).…”
Section: Regulation Of Ado Uptake By Phosphatementioning
confidence: 92%
“…Most of the intracellular radioactivity in the cultured cells was associated with purine nucleoside triphosphates and very little with monophosphates (Table 4). This relative independence of purine phosphoribosylation in the cultured cells on extracellular phosphate may be related to inherently higher intracellular levels of phosphate (5-15 mM; Bowen and Levinson, 1982;McIvor et al, 1985) and consequently of P-Rib-PP in these cells than found in erythrocytes as well as a tighter regulation of the intracellular phosphate concentration. For example, incubation of Novikoff cells in phosphate-free medium for several hours at 37°C has little effect on the intracellular phosphate concentration (McIvor et al, 1985).…”
Section: Regulation Of Ado Uptake By Phosphatementioning
confidence: 92%
“…1). Values for the trapped volume obtained by this method were found to be no different from those measured using [3H]methoxyinulin as an extracellular space marker (Bowen and Levinson, 19821, based on a paired difference test of determinations made on the same cell suspensions (P > 0.95, N = 30). The volume of trapped medium obtained in this manner was used to make the appropriate correction in the calculations of cellular water and P,.…”
Section: Pi Transportmentioning
confidence: 99%
“…However, when pH, is reduced, transport is stimulated to the same extent and with the same time course and kinetic characteristics as in the presence of Na+. Thus, H + stimulated Pi transport does not require Na+, raising the possibility that the Na+-independent component is mediated by the anion (CI-) exchanger.The transport of inorganic phosphate (Pi) by the plasma membrane of Ehrlich ascites tumor cells requires the presence of Na' to achieve a maximal rate (Bowen and Levinson, 1982). Similar observations have been made in a variety of other tissues (Brown and Lamb, 1975;Berner et al, 1976;Anner et al, 1976;Hamilton and Nilsen-Hamilton, 1978;Lever, 1980; Cheng and Sacktor, 1981).…”
mentioning
confidence: 79%
“…In contrast, the Na f -dependent component of Pi transport exhibits saturation kinetics with respect to both Pi and Na+. The Ks for Pi is 0.12 mM at pH 7.4 (Bowen and Levinson, 1982).…”
Section: Discussionmentioning
confidence: 99%